Bodyweight and body condition scores of Australian British shorthaired cats, 2008–2017 - Murphy, B. J.; Stevenson, M. A.; Mansfield, C. S. (Frontiers in Veterinary Science, 2023)
Obesity is the most common nutritional problem in companion animals today, and Australian British shorthair (BSH) cats have been shown to have a greater likelihood of being overweight relative to other cat breeds. The objectives of this research were to quantify bodyweight (BW) and body condition scores (BCSs) of BSH cats attending first opinion practice in Australia for the period 2008-2017 and to determine if: (1) being classified as overweight was associated with geographical location (urban versus rural and socio-economic index); and (2) BW recorded in the first 12 months of life was associated with length of life beyond 12 months. Electronic medical records from BSH cats presenting were obtained from VetCompass Australia and used for BW and BCS analysis.Desexed males (𝑛 = 971) had the highest mean BW followed by entire males (𝑛 = 79), desexed females (𝑛 = 815), and entire females (𝑛 = 82). The desexed males, desexed females, and entire females had a mean BCS classified as overweight using a 1-to-9 point BCS scale. The entire male population was the only group with a mean BCS classified as ideal.No statistically significant association between BW and urban-rural status and no consistent trend between BW and socioeconomic deprivation was found. For cats with at least one BW measurement in the first 12 months of life that was <3.3 kg, the age when 20 percent of the group had died or were euthanised was 12.3 (95% CI 11.7 to 13.1) years. For cats with at least one BW measurement in the first 12 months of life that was ≥3.3 kg age, the age when 20 percent of the group had died or were euthanised was 6.6 (95% CI 5.2 to 6.6) years. This was a substantial clinical difference in survival.The study concluded that a large proportion of BSH cats attending first opinion veterinary clinics in Australia between 2008 and 2017 (48%) were classified as overweight. Cats less than 12 months of age that were greater than 3.3 kg had a shortened lifespan beyond 12 months of age compared with cats that were less than 3.3 kg.